Capturing the rapid response of sediments to low-oxygen conditions with high temporal resolution gas concentration measurements - Chua, Emily J.; Fulweiler, Robinson W. (Frontiers in Environmental Science, 2023)
Low-oxygen conditions plague coastlines worldwide. At present, little is known about how the transition from normoxic to low or even no oxygen conditions alters sediment biogeochemical cycling and ultimately ecosystem functioning. Conventional sediment core incubations cannot capture rapid (<hourly) changes in biogenic gas fluxes that may occur due to oxygen depletion. To better constrain the response of sediments to hypoxia, we employed a novel flow-injection system coupled to a membrane inlet mass spectrometer to quantify fluxes oxygen, dinitrogen, and methane across the sediment-water interface from a temperate estuary (Narragansett Bay, Rhode Island, United States). We evaluated how sediments from a site more impacted by nitrogen pollution compare to one less impacted by nitrogen in response to organic matter addition. Our system is able to sample every 10 minutes, allowing us to cycle through triplicate core measurements roughly every 30 minutes to track the response of sediments to increasing hypoxic severity. The high temporal-resolution data revealed dynamic changes in sediment-water gas fluxes, suggesting that reactive nitrogen removal is enhanced under mild hypoxia but dampened under prolonged hypoxia to anoxia. Further we found that organic matter loading enhances both net denitrification and methane emissions. Ultimately, our approach represents a powerful new tool for advancing our knowledge of short-term temporal dynamics in benthic biogeochemical cycling.